Improving English Reading Skill through the Directed Reading Thinking Activity (DRTA) Strategy at Nursing Student - Asef Wildan Munfadlila (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2021)
Reading is an integral part of the entire learning process experienced by students while studying at school. Reading can increase vocabulary and knowledge of grammar and syntax. DRTA (Directed Reading Thinking Activity) is a technique that encourages students to make predictions while they are reading. The research was to describe the process reading skill understanding and improving, implementing reading strategy (DRTA) at 3rd grade students in the 5th semester of the Bachelor of Nursing study program STIKES Bina Sehat PPNI Mojokerto. The research method was Classroom Action Research (CAR) with one cycle. The result shows that The Directed Reading Thinking Activity (DRTA) strategy can help students understand the contents of the reading. Students also find it easier to answer the questions posed according to the content of the reading and also easier to retell the contents of the reading they have read using their own language according to their understanding.